Agronursing-Based Care Model as an Approach to Reduce Loss to Follow-Up Cases among People With HIV AIDS in Indonesia: A Perspective - Dicky Endrian Kurniawan; Lantin Sulistyorini; M. Nur Khamid; Indra Sarosa (Nursing and Health Sciences Journal (NHSJ), 2022)
Antiretroviral (ARV) treatment has become the standard of minimal care for people living with HIV. The length of treatment impacts the compliance of PLWHA in accessing and getting treatment. The Indonesian government's strategy in the HIV/AIDS control system is to expand services to the Puskesmas level, from counseling and testing to ARV care/treatment. The problem is that the number of health personnel in charge of the program is limited. The limited number of health workers will impact their ability to follow up with PLWHA to obtain services, especially maintaining ARV consumption. Agronursing is the provision of agricultural-based nursing services in areas of agriculture, plantations, waters, or industrial agriculture. The concept of the agronursing-based care model is by optimizing the duties of nurses in agricultural or rural areas as an extension of the government's program in controlling HIV/AIDS, which is currently still at the Puskesmas level. The agronursing-based care model is an opportunity to reduce loss to follow-up in PLWHA. Implementing the agronursing-based care model includes providing comprehensive nursing care, providing ARV therapy, providing support and counseling, managing the service system for PLWHA, and facilitating outreach and referrals to health centers, hospitals, or NGOs. Further studies are needed to ensure that the agronursing-based care model effectively reduces loss to follow-up in PLWHA and achieves HIV/AIDS control programs.